Penerapan Model Pembelajaran Problem Based Learning dengan Konten Pembelajaran yang Kontekstual untuk Meningkatkan Keterampilan Berpikir Kritis dan Kreativitas Siswa pada Materi Fluida Statis - Elisabeth Bunga Uri Nolowala; Agustina Elizabeth; Bertolomeus Haryanto Agung; Emanuel Berthonaldi (Journal on Education, 2024)
This study aims to enhance the critical thinking skills and creativity of Class XI MIA students in static fluid material by implementing a problem-based learning model with contextual content. The research was conducted at SMAK Santa Maria Monte Carmelo Maumere, with the participants from Class XI MIA in the academic year 2023/2024. Data collection utilized tests to assess students's critical thinking skills and observations to evaluate creativity. The data analysis employed a descriptive quantitative approach. Research findings indicate that the average critical thinking skills score for students is 83, surpassing the minimum completeness criteria (KKM) set by SMAK Santa Maria Monte Carmelo Maumere. Additionally, the average creativity score for students is 68.75%, falling within the good category. These outcomes suggest that the implementation of the problem-based learning model with contextual content effectively enhances the level of critical thinking skills and creativity on Class XI MIA students in static fluid material.